Food structure and moisture transfer : a modeling approach - Guillard, Valerie; Bourlieu, Claire; Gontard, Nathalie (New York : Springer, 2013)
It's well known that the structural characteristics of food materials influence their mass transfer, especially their water transfer properties during such processes as drying, hydration, and storage. In porous cereal-based products, for example, effective water diffusivity is highly affected by the volume fraction and distribution of both solid and gas phases, while in dense food materials, such as fat-based or other edible coatings, it depends on factors that affect the'tightness' of the molecular structure (e.g., free volume, cohesive energy density, crystallinity)
Includes bibliographical references and index.
Keywords: Food -- Moisture; Food -- Composition